Extraction Rate and Energy Efficiency of Supercritical Carbon Dioxide Recovery of Higher Alcohols from Dilute Aqueous Solution. Issue 4 (8th February 2018) - Tompsett, Geoffrey A.; Boock, Jason T.; DiSpirito, Cameron; Stolz, Eric; Knutson, David R.; Rivard, Allison G.; Overdevest, Mark R.; Conlon, Chelsea N.; Prather, Kristala L. J.; Thompson, Janelle R.; Timko, Michael T.
Abstract: New biotechnologies have been developed to produce higher alcohols, including various isomers of butanol, pentanol, and hexanol. The thermodynamic properties of higher alcohols—i.e., low volatility and moderate water solubility—make them good candidates for extraction using supercritical carbon dioxide (scCO2 ). Here, we studied semi‐batch extraction of several representative higher alcohols, including n ‐butanol, n ‐pentanol, and n ‐hexanol from dilute aqueous solutions using scCO2, measuring the initial extraction rates and extraction efficiencies, where the extraction efficiency was defined as the grams of alcohol recovered per gram of scCO2 . In all cases, the extraction kinetics were well described by a simple first‐order disappearance model and the extraction rates were much greater than the published butanol bioproduction rates. Quantitatively, the initial extraction rates and efficiencies, respectively, for both n ‐hexanol and n ‐pentanol were 1.6±0.2 and 1.3±0.1 times greater than that for n ‐butanol. These results were analyzed for semi‐continuous alcohol recovery and compared with previous literature on butanol gas stripping to evaluate the competitiveness of the scCO2 separation strategy. Abstract : Extracting the best : Supercritical carbon dioxide (scCO2) is examined for extraction of higher alcohols from dilute aqueous solutions. The work provides the basis for understanding extraction rates, extraction efficiency, and the purity of the extracted alcohol and could be applied to the future production of biofuels.